Development of Standard Speech Database in Marathi Language for Emotion Recognition System - Shinde, AR; Agnihotri, PP; Khanale, PB (International Journal of Computer Sciences and Engineering, 2014)
The biometrics a trading technology to recognize a person based on the physiological or behavioral characteristics. Emotion Recognition system is a part of Human Computer Interaction. The database has been developed to recognize the emotions of human based on speech trait. While recording speech samples different Marathi words and phrases were considered. These words were very useful to identify the emotions of human being. The emotions such as happy, sad, surprise, angry, disgust, fear and neutral were recorded. In the proposed work seven basic emotions were considered such as happy, sad, angry, surprise, fear, disgust, and neutral. According to this, the words like “Are deva”, “Aare re”, “kiti chan”, “Mast”, “Gapre”, “khatarnak” etc. were used to decide what kind of emotion that human being gave through speech. There were total of 50 speakers out of which 25 male and 25 female speakers were recorded. . In this paper for each emotion four Marathi emotional words were recorded. In this way there were total 28 words by One speaker and total 1400 words (emotional words/phrases) recorded by 50 speakers including male and female speaker were recorded. This paper discusses about the development of Speech database developed at School of Computational Sciences, Solapur University, Solapur.